¿Is Governance a Form of Administration in a Government? -Governability in Colombia 2014 -2016 (2017)
For many years, the definition of governance has become part of the common language, specifically in the academic and political spheres; Being considered the governance as the ability of the governors to effectively and efficiently meet the needs of its governed through tools called public policies and developing plans, programs and investment projects that have the greatest possible impact on communities. A community is more or less governable depending on the credibility of its institutions, while such institutions will be more or less strong depending of the community feels represented in them and is willing to abide by its guidelines and contribute to the development and balanced and equitable growth of its members. In combination with planning, organization, direction and control, could say that governance is a form of government administration. Based on the above, this essay presents the definition of governance, the definition of different administrative theories about it; and it shows in a brief way about how was the governance of the end of the last century and of the earliest of this century, and how governance has been in the last two years in Colombia. The essay concludes with a deliberation about if governance could be considered as a new form or theory of administration.